VERBALIZATION SUFFIXES –IZE –IFY, –ATE, AND –EN IN ENGLISH AND THEIR EQUIVALENCES IN INDONESIAN - Masrul Huda (Publikasi dan UKI Press UKI Toraja., 2023)
The objective of the study is to find the distribution of the suffixes in forming the verbs in English. Then, to find the equivalence for each suffix in Indonesian. The method used in writing is descriptive qualitative. Some ways are conducted in gaining the result such as providing data from Oxford Dictionary and then bilingual dictionary by John Echols and Hasan Shadily (2008) used as the guidance in translating the words. The analysis used is translational method. The results are (1) suffix ize has some equivalences to prefix me-, prefix ber-, affix me-kan, and affix memper-kan. (2) The equivalences of suffixx -ify are prefix me-, affix memper-, and affix me-kan. The third suffix -ate has some equivalences to prefix me-, affix memper-, affix me-kan, and affix me-i, then suffix -en will be prefix me-, affix me-kan, affix me-i, and affix memper-.